Smartphone Screen Recording Apps: An Effective Tool to Enhance Fluency in the English Language - Pardo Soto, Catherine Vanessa; Cisterna Zenteno, Cecilia (Colombian Applied Linguistics Journal, 2019)
This investigation intended to assess the effectiveness of smartphone video recording applications in increasing the speaking fluency of students of English as a foreign language (EFL). The study was conducted on a group of thirty-one 7th grade students aged between 12 and 13 years and enrolled in a subsidised school in Chile. The convenience sampling method was employed to select the participating students and the participants’ manner of communication was analysed through several English speaking sessions in which they used their smartphone video recording applications. Data collection was undertaken through pre- and post-speaking tasks used in this action research. The collected data were examined using a specific analytic rubric and a focus group interview. Data analysis was accomplished via two techniques: a simple percentage analysis and a thematic examination. The findings revealed an increase in the speaking fluency of the participating students, specifically with regard to the ‘pace’ criterion identified in the analytic rubric used to assess improvement in the speaking performance of students as evidenced by video recordings. Also, the results of the focus group interview conducted with the students evidenced the participants’ positive response to the use of smartphone recording video applications in ameliorating their English communication fluency.